Blended-Learning Approach in CAAD: Past Experience and Literature Review for RD&T Project Module on Architecture Representation and Communication Focused in Teaching Architecture and Art - Pedro Neto (2012)
This paper is the result of a research project that began in 2007 - 2008 in the Faculty of Architecture of Porto University (FAUP), which had as aim to adopt a blended learning approach integrating the Centre for Spatial Communication and Representation (CCRE) (http://web.ccre.arq.up.pt) for teaching CAAD to students of Architecture Graduation course in the the 3rd year. The objective is first to evaluate critically how the use of the collaborative platform CCRE worked as a catalyst for engaging the students with their own learning process and for approaching the students and teachers. Second, to understand how this technology has helped to create a new teacher/student interaction, making communication much easier and giving to the students a more active role in the learning process. The paper begins with a short introduction of the program and pedagogical strategy in CAAD and then describes the strategy and model applied in the case study for teaching, referring also the type of digital material and learning tools that were used. Finally, the most significant results for each case study are discussed and a set of conclusions will be drawn in the light of last case study. The results, besides other things, highlight how the learning process that rises from the creative use of an open collaborative platform as CCRE and facebook with a blended learning approach strengthens the teacher's capacity to work as a team and helps to open the university to its city and people.